Comparative physiology and the predictability of evolution in extreme environments - Barts, Nick (Kansas State University, 2020)
The physiological mechanisms underlying adaptation, and how physiological differences observed in natural populations relate to underlying genetic variation, remain largely unknown for many natural systems. My dissertation seeks to close these gaps in knowledge by addressing three major questions: 1) How does variation across levels of biological organization integrate to explain divergence in organismal phenotypes? 2) Are patterns of physiological adaptation predictable across populations experiencing similar sources of selection? 3) What are the evolutionary origins of physiological traits facilitating adaptation to novel environmental conditions? Organisms inhabiting extreme environments are ideal systems to investigate questions about the mechanisms underlying adaptation and the predictability of evolution at molecular scales. These habitats are characterized by harsh physiochemical stressors that often target specific biochemical and physiological pathways, allowing for hypothesis-driven tests of the effects of the stressor on organismal function and trait evolution. Additionally, powerful comparisons can be made between closely related lineages inhabiting extreme and ancestral habitats, which allows for investigations into the predictability of evolution in response to similar sources of selection. In my research, I leveraged a unique study system of fishes that have independently colonized extreme aquatic habitats rich in hydrogen sulfide (H₂S), a naturally occurring toxin that is known to interfere with oxygen transport and mitochondrial function address four objectives: 1) I determined the predictability and repeatability of molecular evolution and changes in gene expression of oxygen transport genes in ten lineages of sulfide-tolerant fishes, 2) I assessed the convergence in biochemical, physiological, and organismal function in pathways exhibiting evidence of molecular evolution and gene expression variation, 3) I measured the functional consequences of genetic variation on the metabolic function of enzymes, mitochondria, and whole organisms to identify the predictability of metabolic evolution across levels of organization and between sulfide-tolerant and -intolerant lineages of fish, and 4) I identified potential adaptive plasticity in gene expression in ancestral freshwater species that may represent pre-adaptations for the colonization of H₂S-rich springs. Through the integration of genomic, biochemical, and organismal data, I found that (1) oxygen transport genes are predictable targets of natural selection in sulfide spring fishes, but the modifications in gene expression and sequence variation were not repeatable across groups, (2) both H₂S detoxification and oxidative phosphorylation are predictable targets of natural selection in H₂S-rich environments, and modification of these integral pathways results in functional differences at the biochemical, physiological, and organismal levels, (3) the degree to which metabolic physiology varies between sulfide-tolerant and -intolerant fish differs depending on the level of organization observed, suggesting that researchers must be cautious when making inferences about function solely from genetic data, and (4) genes exhibiting adaptive plasticity in H₂S detoxification, metabolic pathways, and oxygen sensing may have been pre-adaptations that facilitated colonization of sulfide-rich springs. The research detailed in this dissertation has important implications for how scientists perceive the predictability of both evolution and phenotype, highlighting the role environmental and physiological constraints play in our ability to predict the outcomes of natural variation across habitats and within organisms.
Keywords: Comparative physiology; Mitochondrial adaptation; Hydrogen sulfide; Extreme environments; Metabolism; Convergent evolution